2006
DOI: 10.1074/jbc.m510377200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Active Matrilysin to Cell Surface Cholesterol Sulfate Is Essential for Its Membrane-associated Proteolytic Action and Induction of Homotypic Cell Adhesion

Abstract: Regulation of cell surface molecules by matrix metalloproteinases (MMPs), as well as MMPs-catalyzed degradation of extracellular matrix, is important for tumor invasion and metastasis. Our previous study (Kioi, M., Yamamoto, K., Higashi, S., Koshikawa, N., Fujita, K., and Miyazaki, K. (2003) Oncogene 22, 8662-8670) demonstrated that active matrilysin specifically binds to the surface of colon cancer cells and induces notable cell aggregation due to processing of the cell membrane protein(s). Furthermore, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 37 publications
4
80
0
1
Order By: Relevance
“…These include CD44 heparan sulfate proteoglycan (HSPG), cholesterol sulfate, and CD151. [18][19][20] Cholesterol sulfate is a component of lipid raft and CD151 is a transmembrane 4 superfamily protein that appears in a detergent-insoluble lipid-containing microdomain. To learn the possible docking mechanism of MMP-7, the behavior of the membrane-associated MMP-7(Asp-137) variant was analyzed in the presence of detergent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include CD44 heparan sulfate proteoglycan (HSPG), cholesterol sulfate, and CD151. [18][19][20] Cholesterol sulfate is a component of lipid raft and CD151 is a transmembrane 4 superfamily protein that appears in a detergent-insoluble lipid-containing microdomain. To learn the possible docking mechanism of MMP-7, the behavior of the membrane-associated MMP-7(Asp-137) variant was analyzed in the presence of detergent.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that active MMP-7, but not proMMP-7, efficiently binds to cholesterol sulfate on the cell surface. 19 In contrast, CD151 anchors latent proMMP-7 onto the cell surface, but its affinity to interact with the active form of MMP-7 is relatively low. 20 Therefore, we hypothesized that association of the pro-form of MMP-7(Asp-137) variant to CD151 at the cell surface provides the opportunity for MMP-7 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, proteinases, such as MMPs, would likely be anchored to the cell membrane, thereby maintaining a locally high enzyme concentration and targeting their catalytic activity to specific substrates within the pericellular space. In addition to the membrane-bound MMPs, several examples of specific cell-MMP interactions have been reported, such as the binding of MMP-2 to the α v β 3 integrin (Brooks et al, 1996), MMP-1 to the α 2 β 1 integrin Stricker et al, 2001), MMP-9 to CD44 (Yu and Stamenkovic, 2000), and MMP-7 to surface proteoglycans (Yu and Woessner, 2000;Yu et al, 2002), cholesterol (Yamamoto et al, 2006), and CD151 (Shiomi et al, 2005). As suggested for CD44 (Yu and Stamenkovic, 2000) and the α 2 β 1 integrin ), these membrane anchors may act as accessory factors that mediate both pro-enzyme activation and binding of both substrate and proteinase, thereby increasing the probability of proteolysis (Fig.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…After a 5-h induction, E. coli cells were broken in 50 mM Tris-HCl, pH 8.0 containing 50 mM NaCl and 5 mM EDTA with a sonicator, and the resultant inclusion bodies were collected by centrifugation. Solubilization of the inclusion bodies with guanidine-HCl followed by refolding by rapid dilution method was performed as described previously (35,36). In the case of GST fusion proteins, the refolded proteins were incubated with thrombin to remove the N-terminal GST region.…”
Section: Methodsmentioning
confidence: 99%